Prepapillary Vascular Loops Complicated by Suspected Macroaneurysm Rupture - Kei Akaiwa; Yoshinori Mitamura; Takashi Katome; Kentaro Semba; Mariko Egawa; Takeshi Naito (Case Reports in Ophthalmological Medicine)
We present a case of prepapillary vascular loops complicated by a suspected macroaneurysm rupture which was treated with intravitreal bevacizumab (IVB). A 62-year-old woman presented with decreased vision and myodesopsia in her left eye. Her best-corrected visual acuity (BCVA) was 0.6 in the left eye. Fundus examination disclosed an elevated, round, and reddish lesion, retinal hemorrhage at the superior aspect of the optic disc, retinal opacification along the superior branch retinal artery, and a small vitreous hemorrhage. Optical coherence tomography showed a serous retinal detachment, and indocyanine green angiography demonstrated prepapillary vascular loops and a hypofluorescent area with hyperfluorescent margins. These findings suggested the presence of a macroaneurysm. No filling of the dye in the aneurysm-like dilatation suggested a blockage of the lumen with a thrombus which might be associated with a branch retinal artery occlusion (BRAO). A diagnosis of prepapillary vascular loops complicated by a suspected macroaneurysm rupture and BRAO was made. Because of a persistent serous retinal detachment, IVB was performed. One month later, the BCVA improved to 1.0. Fundus examination disclosed an organized yellowish-white macroaneurysm and resolution of the serous retinal detachment. We recommend careful monitoring of patients with prepapillary vascular loops because of complications such as macroaneurysm rupture and BRAO.